The neuronal basis of human creativity - Malach, Rafael (Frontiers in Human Neuroscience, 2024)
Human creativity is a powerful cognitive ability underlying all uniquely human cultural and scientific advancement. However, the neuronal basis of this creative ability is unknown. Here I propose that slow, spontaneous fluctuations in neuronal activity, also known as "resting state" fluctuations-constitute a universal mechanism underlying all facets of human creativity. Support for this hypothesis is derived from experiments that directly link spontaneous fluctuations and verbal creativity. Recent experimental and modelling advances in our understanding of the spontaneous fluctuations offer an explanation for the diversity and innovative nature of creativity-which is derived from a unique integration of random, neuronal noise on the one hand with individually specified, deterministic information acquired through learning, expertise training and hereditary traits. This integration between stochasticity and order leads to a process that offers, on the one hand, original, unexpected outcomes, but on the other hand, endows these outcomes with knowledge-based meaning and significance.